2022
DOI: 10.18103/mra.v10i9.3100
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Osteomyelitis and Septic Arthritis in Children

Abstract: Salmonella infections of the bone and joints are very rare. They are common in hemoglobinopathies and immunocompromised children. The diaphysis and metaphysis of the long bones are common sites. The spine pelvis, ribs, and cranium are rare sites. The clinical course is indolent compared to acute osteomyelitis. Serological tests and culture can be used for the diagnosis. Radiographs are frequently negative early in the disease. CT scans and MRI scans can be used in certain cases. The majority of cases can be ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…82 The incidence increases to between 1.5% and 12% in children with sickle cell disease. 83 It is interesting to note that a prior review article by Burnett et al in 1998 indicated a higher ratio (1.4:1) of Salmonella AHOM compared to S. aureus in patients with sickle cell disease. 84 This ratio was even lower than a report from 1981, which reported that 50 out of 68 positive cultures yielded Salmonella.…”
Section: Salmonellamentioning
confidence: 96%
See 1 more Smart Citation
“…82 The incidence increases to between 1.5% and 12% in children with sickle cell disease. 83 It is interesting to note that a prior review article by Burnett et al in 1998 indicated a higher ratio (1.4:1) of Salmonella AHOM compared to S. aureus in patients with sickle cell disease. 84 This ratio was even lower than a report from 1981, which reported that 50 out of 68 positive cultures yielded Salmonella.…”
Section: Salmonellamentioning
confidence: 96%
“…86 However, Salmonella osteomyelitis has been reported as typically affecting the diaphysis of long bones, particularly the femur and humerus, as well as the vertebrae. 82,83…”
Section: Salmonellamentioning
confidence: 99%